Comparison of two doses of primary intravitreal bevacizumab (Avastin) for diffuse diabetic macular edema: Results from the Pan-American Collaborative Retina Study Group (PACORES) at 12-month follow-up (2009)
Background: To report the 12-month anatomic and ETDRS best-corrected visual acuity (BCVA) response after primary intravitreal bevacizumab (Avastin®) (1.25 mg or 2.5 mg) in patients with diffuse diabetic macular edema (DDME). In addition, a comparison of the two different doses of intravitreal bevacizumab (IVB) utilized was made. Methods: We reviewed the clinical records of 82 consecutive patients (101 eyes) with DDME in this interventional retrospective multicenter study. All patients with a minimum follow-up of 12 months (mean 57.6±8.4 weeks) were included in this analysis. Patients underwent ETDRS best-corrected visual acuity (BCVA) testing, ophthalmoscopic examination, optical coherence tomography (OCT), and fluorescein angiography (FA) at baseline and follow-up visits. Results: The mean age of our patients was 59.7±9.3 years. The mean number of IVB injections per eye was three (range: one to six injections) at a mean interval of 14.1±10.5 weeks. In the 1.25 mg group at 1 month BCVA improved from 20/190, logMAR=0.97 to 20/85, logMAR 0.62, a difference that was statistically significant (p=0.0001). This improvement was maintained throughout the 3-, 6-, and 12-month follow-up. The mean final BCVA at 12 months was 20/76, logMAR=0.58 (p less than 0.001), a statistically significant difference from baseline BCVA. Similar BCVA changes were observed in the 2.5 mg group. In the 1.25 mg group, the mean central macular thickness (CMT) decreased from 419.1±201.1 ?m at baseline to 295.11±91.5 ?m at 1 month, 302.1±124.2 m at 5 months, 313.4.1±96.3 m at 6 months, and 268.2±95.5 m at 12 months (plt;0.0001). Similar CMT changes were observed in the 2.5 mg group. Adverse events included transient high blood pressure in one patient (1.2%), transient increased intraocular pressure in one eye (1%), and tractional retinal detachment in one eye (1%). Conclusions: Primary IVB at doses of 1.25 to 2.5 mg seem to provide stability or improvement in BCVA, OCT, and FA in DDME at 12 months. There seems to be no difference in our results between intravitreal bevacizumab at doses of 1.25 mg or 2.5 mg. In addition, our results suggest the need for at least three injections a year to maintain the BCVA results. © Springer-Verlag 2009.